Knockdown resistance mutations predict DDT resistance and pyrethroid tolerance in the visceral leishmaniasis vector Phlebotomus argentipes. - Bruno Gomes; Bidyut Purkait; Rinki Michelle Deb; Aarti Rama; Rudra Pratap Singh; Geraldine Marie Foster; Michael Coleman; Vijay Kumar; Mark Paine; Pradeep Das; David Weetman (Public Library of Science (PLoS), 2017)
BACKGROUND:Indoor residual spraying (IRS) with DDT has been the primary strategy for control of the visceral leishmaniasis (VL) vector Phlebotomus argentipes in India but efficacy may be compromised by resistance. Synthetic pyrethroids are now being introduced for IRS, but with a shared target site, the para voltage-gated sodium channel (VGSC), mutations affecting both insecticide classes could provide cross-resistance and represent a threat to sustainable IRS-based disease control. METHODOLOGY/PRINCIPAL FINDINGS:A region of the Vgsc gene was sequenced in P. argentipes from the VL hotspot of Bihar, India. Two knockdown resistance (kdr) mutations were detected at codon 1014 (L1014F and L1014S), each common in mosquitoes, but previously unknown in phlebotomines. Both kdr mutations appear largely recessive, but as homozygotes (especially 1014F/F) or as 1014F/S heterozygotes exert a strong effect on DDT resistance, and significantly predict survivorship to class II pyrethroids in short-duration bioassays. The mutations are present at high frequency in wild P. argentipes populations from Bihar, with 1014F significantly more common in higher VL areas. CONCLUSIONS/SIGNIFICANCE:The Vgsc mutations detected appear to be a primary mechanism underlying DDT resistance in P. argentipes and a contributory factor in reduced pyrethroid susceptibility, suggesting a potential impact if P. argentipes are subjected to suboptimal levels of pyrethroid exposure, or additional resistance mechanisms evolve. The assays to detect kdr frequency changes provide a sensitive, high-throughput monitoring tool to detecting spatial and temporal variation in resistance in P. argentipes.